Pengaruh Komunikasi Interpersonal Terhadap Motivasi Kerja Volunteer (Studi Pada Yayasan M- Foundation ) - Riyan Ogilvi; Indria Flowerina (CV. ITTC INDONESIA, 2026)
This study is motivated by the importance of interpersonal communication in shaping volunteers’ work motivation within social organizations. Interactions occurring between management and volunteers, as well as among volunteers, serve not only as a means of information exchange but also as a process of meaning construction that influences individuals’ attitudes, enthusiasm, and commitment in performing their roles. The purpose of this study is to examine and analyze the effect of interpersonal communication on volunteers’ work motivation at the M-Foundation. This research employs a quantitative approach using a survey method. The population consists of all active volunteers of the M-Foundation, with the sample determined using the Slovin formula. Data were collected through questionnaires using a Likert scale, while data analysis was conducted using simple linear regression. The results indicate that interpersonal communication has a positive and significant effect on volunteers’ work motivation. This is evidenced by the t-test result, where the t-value (4.415) is greater than the t-table value (1.680), with a significance value of 0.001 (<0.05). Furthermore, the coefficient of determination shows that interpersonal communication contributes 58.2% to volunteers’ work motivation, while the remaining 41.8% is influenced by other variables not examined in this study.